2005
DOI: 10.1021/ma050609q
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Steric Crowding in Phosphorescent Dendrimers

Abstract: A simple convergent procedure has been developed for the formation of sterically encumbered phosphorescent dendrimers. The procedure is demonstrated with the preparation of a first-generation dendrimer composed of a fac-tris(2-phenylpyridyl)iridium(III) core and three dendrons. Each dendron is comprised of a branching phenyl unit with a further four phenyl groups attached. The lack of surface groups on the dendrons was found to reduce solubility and also reduced the level of control over the intermolecular int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…On the other hand, there was a significant irreversible reduction peak at about À 3.18 V. It has been reported that oxidation processes of Ir cyclometalated compounds were assigned to metal-centered orbital and/or to s bond Ir-C orbitals while the reduction process were assigned to ppy-centered orbital [9,52]. Therefore, the potential peak at about À 3.18 V was assigned to ppy reductions and the similar phenomenon (ppy reduction potential between 2.5-3.2 V) was also noted by other reporters [19,53]. However, we cannot find any obvious reduction peaks of the monomer and the complex.…”
Section: Electrochemical Propertiessupporting
confidence: 57%
See 1 more Smart Citation
“…On the other hand, there was a significant irreversible reduction peak at about À 3.18 V. It has been reported that oxidation processes of Ir cyclometalated compounds were assigned to metal-centered orbital and/or to s bond Ir-C orbitals while the reduction process were assigned to ppy-centered orbital [9,52]. Therefore, the potential peak at about À 3.18 V was assigned to ppy reductions and the similar phenomenon (ppy reduction potential between 2.5-3.2 V) was also noted by other reporters [19,53]. However, we cannot find any obvious reduction peaks of the monomer and the complex.…”
Section: Electrochemical Propertiessupporting
confidence: 57%
“…In order to reduce the concentration quenching, bulky groups were introduced into the complex to provide steric hindrance. Ir complex with dendritic structures were reported with satisfactory photoluminescence and electroluminescence quantum yield [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Like the polymeric systems, dendritic structures can be classified as conjugated [50,51,55,[174][175][176][177][178][179][180] and nonconjugated [31,56,[181][182][183] systems. In most cases, a heteroleptic or homoleptic facial tris-cyclometallated iridium(III) complex constitutes the core with two [173,174] or three [50,51,55,56,[172][173][174][175][176][177][178][179][180] ligand-tethered dendritic arms forming the shell. Lin et al reported on a number of bis(cyclometallated) Ir III complexes coordinating dendrimer-functionalized acetoacetonate derivatives as ancillary ligand.…”
Section: Dendritic Systems: a Brief Overviewmentioning
confidence: 99%
“…Based on such tris-cyclometallated Ir III complexes (Scheme 1), Zhou et al fabricated devices exhibiting efficient red emission (h ext ¼ 11.6%, h P ¼ 3.7 lm W À1 ) with high color purity (CIE x,y-coordinates 0.70, 0.30). [50] Samuel and co-workers focused in particular on phenyl-based configurations, [55,56,[172][173][174][175][176][177] while You et al presented a complex equipped with tetraphenyl silyl moieties. [51] The possibility to construct highly defined and very dense assemblies is the most beneficial aspect of dendritic systems.…”
Section: Dendritic Systems: a Brief Overviewmentioning
confidence: 99%
“…5). [66] The addition of surface groups to dendrimers like 19 addressed this problem and good device efficiencies (> 10 %) could be obtained in bilayer devices in which the dendrimer was blended with (CBP). [67] Another direction for dendron development has been to incorporate charge-transporting moieties into the dendron structure, while leaving the emissive chromophore at the core of the dendrimer the same.…”
Section: Role Of the Dendronsmentioning
confidence: 99%